The association between self-regulation and procrastination among private university students in Malaysia - Low, Sew Kim; Sarvarubini Nainee,; Tan, Soon Aun (Penerbit Universiti Kebangsaan Malaysia, 2018)
Academic procrastination is prevalent among university undergraduates and it affects students’ well-being and academic performance. Procrastination has become a concerning phenomenon in recent years and is not taken seriously. As self- regulation is one of the predictors of academic achievement among undergraduates it is often linked to procrastination. Thus, this study aimed to investigate if there are gender differences in self- regulation and procrastination and whether there is a relationship between self- regulation and procrastination among 287 undergraduates from four different private universities in Malaysia. Data were collected using self-report survey with convenience sampling method. The Short Self- Regulation Questionnaire (Carey, Neal, & Collins, 2004) was used to measure self-regulation while procrastination was measured using Tuckman Procrastination Scale (Yockey, 2016). Results of t-test analyses showed that there is no significant gender difference in both self-regulation and procras-tination. Moderate significant negative relationship was found between self-regulation and procrastina-tion. Hence the findings reflect that self-regulation could predict procrastination where students with high self-regulation will tend to procrastinate less. Therefore, self-regulation strategies and interven-tions should be taught to undergraduates in order to further enhance their self-efficacy as well as to have intrinsic motivation to be more goal-directed which could be aimed to reduce academic procrastination.